Suitability of Antonio Donnanno’s Basic Pattern System to Indonesian Women’s Ideal Body Shape - Rahman, Wulandari Mulia; Nelmira, Weni (Gorga : Jurnal Seni Rupa, 2024)
Antonio Donnanno's basic pattern system is an Italian pattern found in Antonio Donnanno's 2014 creation book. The special feature of this basic pattern system is that there is a dart on the shoulder of the front body and the neck of the back body. This research is motivated by the problem of not knowing the suitability of this basic pattern on the ideal body shape of Indonesian women. The purpose of this research is to describe the weaknesses, how to improve them, and the suitability of Antonio Donnanno’s system on the ideal body shape of Indonesian women. This research is an applied research with the object of research on the basic pattern of the Antonio Donnanno system on the ideal body shape of Indonesian women with a height of 168 cm and a weight of 58 kg. The research instrument was a questionnaire using a Likert scale. The assessment was carried out by 3 panelists, namely fashion lecturers who are experts in the field of patterns by fitting. The data analysis technique used descriptive quantitative. The results showed that the basic pattern of the Antonio Donnanno system on the ideal body shape of Indonesian women had several weaknesses, including: 1) neck circumference of the front waist length up 1 cm , 2) front torso width 2 cm excess, and 3) hip side 2 cm excess. How to fix them, namely: 1) the neck circumference of the front waist length is increased by 1 cm, 2) the front torso width is reduced by 1 cm, and 3) the side of the hip is formed without increasing 5 cm. Therefore, it can produce a basic pattern that is suitable for the ideal body shape of Indonesian women. This is based on the percentage obtained in fitting II, which is 95% very suitable. The suitability of the pattern is obtained by adjusting the pattern by fixing the weaknesses of the basic pattern of the Antonio Donnanno system.